Collections as Relations (Taylor & Francis, 2025)
This book explores anthropological and global art collections as a catalyst, a medium, and an expression of relations. Relations—between and among objects and media, people, and material and immaterial contexts—define, configure, and potentially transform collection-related social and professional networks, discourses and practices, and increasingly museums and other collecting institutions themselves. The contributors argue that a focus on the—often contested—making and remaking of relations provides a unique conceptual entrypoint for understanding collections’—and ‘their’ objects’ and media’s—complex histories, contemporary webs of interactions, and potential futures. The chapters examine the local, translocal, and transregional relations of collections with regard to their affective, aesthetic, performative, and socio-moral qualities and situate them in the larger geopolitical constellations of precolonial, colonial, and postcolonial settings. Together they investigate ongoing shifts in the relations of collections and collecting institutions by identifying alternative approaches to conceive of, and deal with, anthropological and global art collections, objects, and media in the future. The book is of interest to scholars from anthropology, global art history, museum studies, and heritage studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.